Pay-for-Delay Arrangements in EU Competition Law : The Interface Between Patent Protection and Restrictions of Competition in the Pharmaceutical Sector - Skottman, Jerdi (My University, 2025)
The pharmaceutical sector holds a special position in the EU internal market as an industry that is both highly regulated and heavily reliant on intellectual property rights. Patent protection and supplementary protection certificates safeguard originator companies’ returns on costly research and development, but they also create tensions with competition law, which seeks to protect consumer welfare and access to medicines. One manifestation of this tension is the so-called pay-for-delay agreement, in which an originator transfers value to a generic competitor in exchange for delaying market entry. This thesis analyses how EU competition law, in particular Article 101 TFEU, applies to such agreements, and how courts have drawn the line between legitimate patent settlements and unlawful restraints of competition. The study uses the legal dogmatic method (de lege lata), complemented by a critical de lege ferenda perspective to identify shortcomings and propose improvements. Sources include EU legislation, case law from the Court of Justice and the General Court, Commission decisions, and leading legal literature. The findings show that while most patent settlements do not raise concerns, a small minority restrict entry and transfers value, thereby posing risks to competition and consumers. The thesis concludes that while “by object” assessment has an established role, cases involving genuine patent disputes or uncertainty would benefit from an effects-based approach, which would provide more precise guidance for both enforcement and industry.

Lääketeollisuus on EU:n sisämarkkinoilla erityinen toimiala, joka on sekä tiukasti säännelty että vahvasti riippuvainen immateriaalioikeuksien tarjoamasta suojasta. Patentit ja lisäsuojatodistukset turvaavat alkuperäisvalmistajien investoinnit kalliiseen tutkimukseen ja tuotekehitykseen, mutta ne voivat olla ristiriidassa kilpailuoikeuden tavoitteiden kanssa, joiden ytimessä on kuluttajien hyvinvointi ja lääkkeiden saatavuus. Näiden jännitteiden näkyvin muoto on niin sanottu pay-for-delay-sopimus, jossa rinnakkaisvalmistajan markkinoille tulo viivästyy vastineeksi arvonsiirrosta alkuperäisvalmistajalta. Tutkielma tarkastelee, miten EU:n kilpailuoikeus ja erityisesti SEUT 101 artikla soveltuvat tällaisiin sopimuksiin sekä miten tuomioistuimet erottavat hyväksyttävät patenttisovut kilpailunrajoituksista. Menetelmänä käytetään oikeusdogmaattista lähestymistapaa (de lege lata), jota täydennetään kriittisellä de lege ferenda -näkökulmalla. Lähteinä käytetään EU-lainsäädäntöä, unionin tuomioistuinten ja komission ratkaisuja sekä keskeistä oikeuskirjallisuutta. Tutkielma päätyy siihen, että vaikka by object -arvioinnilla on vakiintunut asemansa, tapaukset, joissa on kyse aidosta patenttiriidasta tai epävarmuudesta, hyötyisivät vaikutusperusteisemmasta arvioinnista. Tämä antaisi selkeämpää ohjausta sekä viranomaisille että yrityksille.
Keywords: Competition law, intellectual property law, patent law, pay-for-delay agreements, pharmaceutical industry regulation, kilpailuoikeus, immateriaalioikeus, patenttioikeus, pay-for-delay -sopimukset, lääketeollisuuden sääntely